Investigation of Functional Ageing of GNP/Ag Conductive Ink under Torsional Conditions - Salim, Mohd Azli; Hussain, Muhammad Arieef; Masripan, Nor Azmmi; Md. Saad, Adzni; Akop, Mohd Zaid; Photong, Chonlatee (International Journal of Integrated Engineering, 2024)
This study evaluated the ageing effects after enduring a cyclic torsional test on electrically high thermal Graphene Nanoplates (GNP)/Ag conductive ink. The Graphene Nanoplates (GNP) hybrid formulation contained silver flake (Ag) as an additional filler, 1-butanol and terpineol as organic solvents for the paste, and ethanol as a chemical solvent for the powder GNP hybrid synthesis. An in-house torsional cyclic test rig acted as an experimental apparatus to hold cyclic torsional tests in measuring the resistivity value of GNP/Ag conductive ink. The sample endured 1000, 2000, and 4000 cycles of repetitive cyclic torsion. The sample was left unattended in a controlled environment for ageing process observation in 15 weeks. Resistivity values for both tests were obtained by using a two-point probe multimeter. Data from the cyclic torsional test showed an increase in average resistivity as the cycles prolonged until 4000 cycles. The outcome of these experiments proved that Graphene Nanoplates (GNP)/Ag conductive ink manages to withstand material deformation and remain electrically stable after experiencing cyclic twisting and the ageing process. The recorded SEM images of the ink layer microstructure surface showed a direct correlation with the obtained sheet resistivity data. The samples that produced high sheet resistivity showed the presence of microcracks and defects on the ink layer The results of this study imply that repeated twisting in a thin film may lead to different mechanical and material modifications, thereby influencing its electrical and mechanical properties, which is vital to developing more reliable and stable stretchable electronics. Additional research on various twisting angles and ink compositions is recommended to have a more profound understanding of the characteristics and features of GNP/Ag conductive ink.